NILAI MORAL DALAM NOVEL KOMET MINOR KARYA TERE LIYE - Shinta May Adella Putri (Universitas Batanghari, 2020)
This research aims at describing moral values which are related with the relationship of human with other human which consists of caring, help each other, deliberation, living in harmony, forgiving, keeping a promise, and respecting others. This research uses qualitative descriptive approach which describes particular event with words or the situational context of the subject in one particular situation. The results of this study show that moral values that include the existence of caring, help each other, deliberation, living in harmony, forgiving, keeping a promise, respecting others, found in the novel Komet Minor by Tere Liye. The quotations relating to the seven forms of moral value are more than 57 quotations. The form of dominant moral value is 18 quotations which found in the value of caring for others while the form of the least moral value is promise with 1 quotation. It is hoped that the value found can be a material of knowledge and learning for literary reader. The characters in the novel Komet Minor are Batozar, Seli, Ali, the crown, Bibi Nay, Putri, Raib, Uncle Kay. In the novel of Komet Minor the most dominant character is Batozar.